LAW, RAPPING AND SOCIAL JUSTICE: RETHINKING TRUTH IN CONTEMPORANEITY - Fagundes, Mari Cristina de Freitas; Henning, Ana Clara Correa; Kyrillos, Gabriela M.; Colaço, Thais Luzia (European Scientific Journal, ESJ, 2014)
Our criminal justice system produces socially naturalized truths which authorize certain subjects’ discourse, and silence others’. Rapping, as a counterculture, produces resistance from peripheral spaces in the complex power and knowledge net around us. Rap lyrics problematize a form of violence present even inside the state action, either as classifying subjects or in it’s so-called democratic discourse. Those questions are reasoned in this paper, in bibliographic contribution and compositions analysis in this genre.